REPRESENTASI MATEMATIS SISWA DALAM PEMECAHAN MASALAH PERBANDINGAN TRIGONOMETRI PADA SEGITIGA SIKU-SIKU DITINJAU DARI KECERDASAN LOGIS MATEMATIS, LINGUISTIK DAN VISUAL SPASIAL - Hitalessy, Merlin; Mataheru, Wilmintjie; Ayal, Carolina Selfisina (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2020)
One of the skills needed in learning mathematics is the ability to solve mathematical problems. In solving problems in mathematics learning, mathematical representation is needed by students in the problem solving process. Students tend to use mathematical representations, but sometimes they don't understand what they are doing. In general, mathematical representations also play an important role in improving mathematical competence. Beside the ability of representation, students also have intelligence, including mathematical logical intelligence, linguistics and visual spatial. This research is descriptive with qualitative approach that aimed to describe the complete mathematical representation of vocational high school students in solving a quadratic equation in terms. The research phase begins with the selection of research subjects were determined by gender and math skills test results were similar. Having chosen the subject and the continuation of the problem solving quadratic equations and interviews. The validity of the data using a triangulation of time that is giving the task of solving a quadratic equation are equal at different times. The results of this study as the mathematic description shows that vocational high school students in solving quadratic equations problem according to Polya step problem solving